Jungle friends - Winskill, John; Disney Global Artists (New York Random House, 2014)
Easy-to-read text introduces a number of Mowgli's friends from the animated Disney version of The Jungle Book
English Stories
2 13 23
Keywords: Animals -- Fiction; Jungles -- Fiction; India -- Fiction